2001
DOI: 10.1096/fj.00-0730fje
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant amplification of A 2A receptor signaling in striatal cells expressing mutant huntingtin

Abstract: Huntington's disease (HD) is a neurodegenerative disorder caused by expansion of a CAG repeat in the gene encoding for Huntingtin (Htt), which results in progressive degeneration of the striatal GABAergic/enkephalin neurons. These neurons express both the A2A and D2 receptors, which stimulate and inhibit adenylyl cyclase, respectively. In this study we analyzed the possibility of an involvement of the A2A receptor and its signaling components in the pathogenesis of HD. We report here that striatal cells expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…This selective neuronal vulnerability occurs despite ubiquitous expression of mutant and normal huntingtin suggests that these receptors might play a pathogenetic role in HD (Popoli et al, , 2008. Changes in A 2A receptor expression and signalling in both experimental models of HD (Tarditi et al, 2006) and in peripheral blood circulating cells of HD patients (Varani et al, 2001(Varani et al, , 2007) support this hypothesis. However, the functional significance of the aberrant A 2A receptor phenotype in HD is complicated by conflicting data about the potential neuroprotective and neurodegenerative effects of these receptors in the brain.…”
Section: Huntington's Disease (Hd)mentioning
confidence: 97%
“…This selective neuronal vulnerability occurs despite ubiquitous expression of mutant and normal huntingtin suggests that these receptors might play a pathogenetic role in HD (Popoli et al, , 2008. Changes in A 2A receptor expression and signalling in both experimental models of HD (Tarditi et al, 2006) and in peripheral blood circulating cells of HD patients (Varani et al, 2001(Varani et al, , 2007) support this hypothesis. However, the functional significance of the aberrant A 2A receptor phenotype in HD is complicated by conflicting data about the potential neuroprotective and neurodegenerative effects of these receptors in the brain.…”
Section: Huntington's Disease (Hd)mentioning
confidence: 97%
“…Interestingly, in clear contrast with what occurs for A 1 Rs, chronic stressful stimuli directed to the basal ganglia cause an increased expression and density of A 2A Rs, as observed in animal models of Parkinson's disease (e.g., [208,209]) and in Parkinsonian patients ( [210]; see also [211,212]). It is also possible that the expression of A 2A Rs might also increase in animal models and patients with Huntington's disease, since the expression of A 2A Rs is increased in neurons over-expressing huntingtin [213]. However, the major loss of medium spiny neurons in this condition may mask the increased density of A 2A Rs in the remaining viable neurons [211,214,215].…”
Section: Modification Of Adenosine Metabolism On Stressful Conditionsmentioning
confidence: 99%
“…Interestingly, recent studies have demonstrated that application of topical adenosine A2A receptor agonists promotes more rapid wound closure in skin lesions. In the CNS, blockade of 2A receptors has been shown to induce protection in various models of neurodegenerative diseases (Varani et al, 2001), and in this regard it is of interest to note that Brambilla et al (2003) have shown that exposure of primary rat striatal astrocytes to a selective A(2A) antagonist protected against induction of astrogliosis in vitro by bFGF. However, these authors also showed that the direct activation of A(2A) adenosine receptors by selective receptor agonists was not sufficient to induce a reactive astrogliosis, suggesting that the A(2A) receptor needs to act in concert with other bFGF-induced genes to trigger the formation of reactive astrocytes.…”
Section: Ionotropic P2x Receptors Cd73 A2a and Cd38mentioning
confidence: 99%